Asuhan Keperawatan Pada Ny. R Dengan Defisit Perawatan Diri di RSJP dr. Soeharto Heerdjan Jakarta - Ayu Martianingrum; Christina Trisnawati; Rahaju Ningtyas (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background : Self care deficit is a condition when an individual has barriers to taking care of himself independently starting from bathing, wearing clothes properly, being able to eat and drink independently, to defecating properly. According to the World Health Organization, the incidence of mental health with a prevalence is still relatively high, reaching 25% of the total population of Indonesia who experience psychiatric problems, as many as 1% experience severe mental disorders, young people are more at risk of developing psychiatric problems, counting 450 million people in the world are affected by health problems that attack the nerves and even behavior. One of the treatments for patients with self-care deficits is by applying SP 1-4 for self-care deficits. Objective: Provide nursing care to patients with self-care deficits. Results: The evaluation results show good self-care in patients with self-care deficits. Conclusion: Based on the results of the case study, it was found that the patient was able to perform self-care independently.